Tìm x:
1/2.(x+2/3)+1/3.(x+3/4)+1/4.(x+4/5)=3
Tìm x, biết:
a.1/4+3/4.x=3/2-x
b.3/5.x-1/4=1/10.x-1/2
c.3x-3/5=x-1/4
d.3/2.x-2/5=1/3.x-1/4
`@` ` \text {Ans}`
`\downarrow`
`a,`
`1/4+3/4*x=3/2-x`
`=> 1/4 + 3/4x - 3/2 + x = 0`
`=> (1/4 - 3/2) + (3/4x + x) = 0`
`=> -5/4 + 7/4x = 0`
`=> 7/4x = 5/4`
`=> x = 5/4 \div 7/4`
`=> x = 5/7`
Vậy, `x=5/7`
`b,`
`3/5*x-1/4=1/10*x-1/2`
`=> 3/5x - 1/4 - 1/10x + 1/2 = 0`
`=> (3/5x - 1/10x) + (-1/4 + 1/2)=0`
`=> 1/2x + 1/4 = 0`
`=> 1/2x = -1/4`
`=> x = -1/4 \div 1/2`
`=> x = -1/2`
Vậy, `x=-1/2`
`c,`
`3x-3/5=x-1/4`
`=> 3x - 3/5 - x + 1/4 = 0`
`=> (3x - x) - (3/5 - 1/4) = 0`
`=> 2x - 7/20 = 0`
`=> 2x = 0,35`
`=> x = 0,35 \div 2`
`=> x = 7/40`
Vậy, `x=7/40`
`d,`
`3/2*x-2/5=1/3*x-1/4`
`=> 3/2x - 2/5 - 1/3x + 1/4 = 0`
`=> (3/2x - 1/3x) - (2/5 - 1/4) = 0`
`=> 7/6x - 3/20 = 0`
`=> 7/6x = 3/20`
`=> x = 3/20 \div 7/6`
`=> x = 9/70`
Vậy, `x=9/70`
`@` `\text {Kaizuu lv uuu}`
tìm x
a) X x 3/4 = 1/5 b) 3/7 x X = 2/5 c) 1/3 + 2/9 = 2/12 x X
d) 4/15 x X - 2/3 = 1/5 e) x : 1/7 = 2/3 f) 1/9 : x = 7/3 j) 1/4 + 5/12 = 8/3 : x
h) 7/4 : X - 1/2 = 1/5
a: x*3/4=1/5
=>x=1/5:3/4=1/5*4/3=4/15
b: x*3/7=2/5
=>x=2/5:3/7=2/5*7/3=14/15
c: 1/3+2/9=2/12x
=>1/6x=3/9+2/9=5/9
=>x=5/9*6=30/9=10/3
d: 4/15*x-2/3=1/5
=>4/15*x=2/3+1/5=10/15+3/15=13/15
=>4x=13
=>x=13/4
e: x:1/7=2/3
=>x=2/3*1/7=2/21
f: 1/9:x=7/3
=>x=1/9:7/3=1/9*3/7=3/63=1/21
j: 1/4+5/12=8/3:x
=>8/3:x=3/12+5/12=8/12=2/3
=>x=4
h: =>7/4:x=1/5+1/2=7/10
=>x=7/4:7/10=10/4=5/2
bài1. tính : a. 3 và 2/5 - 1/2 b. 4/5 + 1/5 x 3/4 c. 3 và 1/2 x 1 và 1/7 d. 4 và 1/6 : 2 và 1/3
bài2 : tính : a. 3 x 1/2 +1/4 x1/3 b. 1 và 4/5 - 2/3 : 2 và 1/3
bài 3 tìm x: a. X x 4/5 = 2 và 1/2 b. x : 3/2 = 11/4 - 5/2
sos
Bài 1
a) 3 2/5 - 1/2
= 17/5 - 1/2
= 34/10 - 5/10
= 29/10
b) 4/5 + 1/5 × 3/4
= 4/5 + 3/20
= 16/20 + 3/20
= 19/20
c) 3 1/2 × 1 1/7
= 7/2 × 8/7
= 4
d) 4 1/6 : 2 1/3
= 25/6 : 7/3
= 25/14
Bài 2
a) 3 × 1/2 + 1/4 × 1/3
= 3/2 + 1/12
= 18/12 + 1/12
= 19/12
b) 1 4/5 - 2/3 : 2 1/3
= 9/5 - 2/3 : 7/3
= 9/5 - 2/7
= 63/35 - 10/35
= 53/35
Bài 1
a) 3 2/5 - 1/2
= 17/5 - 1/2
= 34/10 - 5/10
= 29/10
b) 4/5 + 1/5 × 3/4
= 4/5 + 3/20
= 16/20 + 3/20
= 19/20
c) 3 1/2 × 1 1/7
= 7/2 × 8/7
= 4
d) 4 1/6 : 2 1/3
= 25/6 : 7/3
= 25/14
bủh
TÌM X, BIẾT:
a) 3 . ( 1/2 - x ) + 1/3 = 7/6 - x
b) 4 . ( 1/2 - x ) - 5 . ( x - 3/10 ) = 7/4
c) -3/2 . ( 4/5 - 2/3 ) + x = 4 . ( x - 1/2 )
d) 2 . ( 3/2 - x ) - 1/3 = 7x - 1/4
e) 1/5 . ( -3/5 -10 ) + 5x = x - 2/3
f) -3/2 . ( 5 - 1/6 ) + 4 . ( x - 1/2 ) = 1
~ PLEASE HELP ME ~
Nguyễn Trà My
Phần a)
\(3\times\left(\frac{1}{2}-x\right)+\frac{1}{3}=\frac{7}{6}-x\)
\(32-3x+13=76-x\)
\(116-3x=76-x\)
\(116-76=3x-x\)
\(46=2x\)
\(x=46\div2\)
\(x=13\)
a) \(3.\left(\frac{1}{2}-x\right)+\frac{1}{3}=\frac{7}{6}-x\)
\(3.\left(\frac{1}{2}-x\right)+x=\frac{7}{6}-\frac{1}{3}\)
\(\Rightarrow\frac{3}{2}-3x+x=\frac{5}{6}\)
\(-3x+x=\frac{5}{6}-\frac{3}{2}\)
\(2x=-\frac{2}{3}\)
\(x=-\frac{2}{3}:2\)
\(x=-\frac{1}{3}\)
tìm x
a) -1/8 = 3/x b) x/3 = 3/x c)3/4 . x = 1 và 1/2
d) x - 3/10 = 7/15 : 3/5 e) -4/7 - x = -8/3 . 3/7
f) 4/7 . x - 2/3 = 1/5 g) 2/3 + 1/3 : 3 x = 1/5
h) 2/9 - 7/8 x=1/3 j) (2 và 4/5 x - 50) : 2/3 = 51
\(a,\dfrac{-1}{8}=\dfrac{3}{x}\\ \dfrac{3}{-24}=\dfrac{3}{x}\\ x=-24\\ b,\dfrac{x}{3}=\dfrac{3}{x}\\ x.x=3.3\\ x^2=9\\ x=\pm3\\ c,\dfrac{3}{4}.x=1\dfrac{1}{2}\\ \dfrac{3}{4}.x=\dfrac{3}{2}\\ x=\dfrac{3}{2}:\dfrac{3}{4}\\ x=2\\ d,x-\dfrac{3}{10}=\dfrac{7}{15}:\dfrac{3}{5}\\ x-\dfrac{3}{10}=\dfrac{7}{9}\\ x=\dfrac{7}{9}+\dfrac{3}{10}\\ x=\dfrac{97}{90}\\ e,\dfrac{-4}{7}-x=\dfrac{-8}{3}.\dfrac{3}{7}\\ \dfrac{-4}{7}-x=\dfrac{-8}{7}\\ x=\dfrac{-4}{7}+\dfrac{8}{7}\\ x=\dfrac{4}{7}\\ \)
f: =>x*4/7=1/5+2/3=3/15+10/15=13/15
=>x=91/60
g: =>1/3:3x=1/5-2/3=-7/15
=>3x=-5/7
=>x=-5/21
h: =>7/8x=-1/9
=>x=-1/9:7/8=-1/9*8/7=-8/63
j: =>(2,8x-50)=34
=>2,8x=84
=>x=30
Tìm x biết
a,(2-x)-(2.x-5/2)-|-2|=x-1/4
b.2.(x-1/3)-1/3.x=-1/4-x
c,3/2:/-1|3.x+1/3|/=|5/3-2
d,(3/4-2.x)4-2=79
e,(-4)mũ x+3-1=15
Tìm x, biết :
a) (x-2)3 +6(x+1)2-x3+12=0
b) (x-5) (x+5) - (x+3)2+3(x-2)2=(x+1)2- (x+4)(x-4)+3x2
c) (2x+3)2 +(x-1)(x+1)=5(x+2)2-(x-5)(x+1)+(x+4)
d) (1-3x)2-(x-2)(9x+1)=(3x-4)(3x+4)-9(x+3)2
Giúp mk với ạ, mk cảm ơn !
a) (x-2)3+6(x+1)2-x3+12=0
\(\Rightarrow\)x3-6x2+12x-8+6(x2+2x+1)-x3+12=0
\(\Rightarrow\)x3-6x2+12x-8+6x2+12x+6-x3+12=0
\(\Rightarrow\)24x+10=0
\(\Rightarrow\)24x=-10
\(\Rightarrow\)x=\(\dfrac{-10}{24}=\dfrac{-5}{12}\)
b)(x-5)(x+5)-(x+3)2+3(x-2)2=(x+1)2-(x-4)(x+4)+3x2
\(\Rightarrow\)x2-25-(x2+6x+9)+3(x2-4x+4)=x2+2x+1-(x2-16)+3x2
\(\Rightarrow\)x2-25-x2-6x-9+3x2-12x+12=x2+2x+1-x2+16+3x2
\(\Rightarrow\)3x2-18x-22=3x2+2x+17
\(\Rightarrow\)3x2-18x-22-3x2-2x-17=0
\(\Rightarrow\)-20x-39=0
\(\Rightarrow\)-20x=39
\(\Rightarrow\)x=\(-\dfrac{39}{20}\)
c) (2x+3)2 +(x-1)(x+1)=5(x+2)2-(x-5)(x+1)+(x+4)
⇒4x2+12x+9+x2-1=5(x2+4x+4)-(x2+x-5x-5)+x+4
⇒5x2+12x+8=5x2+20x+20-x2-x+5x+5+x+4
⇒5x2+12x+8-5x2-20x-20+x2+x-5x-5-x-4=0
⇒x2-13x-21=0
tìm x biết
(2/5-x) : 4/3 +1/2 =-4
(-3 +3/x - 1/3 ) : ( 1+ 2/5 2/3 ) = -5/4
-3x/4 .( 1/x +2/7 ) =0
3 - 1-1/2/1+1/x= 5/3
a,1/3 .(x-2/5)=3/4 b, 7/3:(x-2/3)=4/5 c,1/3.(x-2/5)=4/5 d, 2/3.(x-1/2)-1/4.(x-2/5)=7/3 e,3/7 .(x-2/3)+1/2=5/4.(x-2) f,1/2.(x-3)+1/3.(x-4)+1/4.(x-5)=1/5 g,[2/3.(x-1/2)-4/5]:(x-1/3)=21/5 h, {x-[1/2.(x-3)+11/5]}:(x-1/2)=3/5 i,x.(x-2/5)-(x+2).x+11/4=4/3
a: =>x-2/5=3/4:1/3=3/4*3=9/4
=>x=9/4+2/5=45/20+8/20=53/20
b: =>x-2/3=7/3:4/5=7/3*5/4=35/12
=>x=35/12+2/3=43/12
c: 1/3(x-2/5)=4/5
=>x-2/5=4/5*3=12/5
=>x=12/5+2/5=14/5
d: =>2/3x-1/3-1/4x+1/10=7/3
=>5/12x-7/30=7/3
=>5/12x=7/3+7/30=77/30
=>x=77/30:5/12=154/25
e: \(\Leftrightarrow x\cdot\dfrac{3}{7}-\dfrac{2}{7}+\dfrac{1}{2}-\dfrac{5}{4}x+\dfrac{5}{2}=0\)
=>\(x\cdot\dfrac{-23}{28}=\dfrac{2}{7}-3=\dfrac{-19}{7}\)
=>x=19/7:23/28=76/23
f: =>1/2x-3/2+1/3x-4/3+1/4x-5/4=1/5
=>13/12x=1/5+3/2+4/3+5/4=257/60
=>x=257/65
i: =>x^2-2/5x-x^2-2x+11/4=4/3
=>-12/5x=4/3-11/4=-17/12
=>x=17/12:12/5=85/144
Bài 1. Tìm x, biết:
a/ 1/4.(x-3)+2=1/5
b/ 1/7-2.(x+1)=1/4+2/3
c/ 1/4.(2x+3)-1/9=2/5
d/ 3/2.(x+1)-4/9=2/3
e/ 4/5.(2-3x)+4/7=2và1/3
[Cần gấp ạ!]
a) 1/4(x-3)+2=1/5
1/4.(x-3) = 1/5-2
1/4.(x-3) = -9/5
x-3 = (-9/5):1/4
x-3 = -36/5
x = -36/5+3
x= -21/5